Antiglycating activity of biomimetically synthesized magnetic copper ferrite nanoparticles: inhibition of methylglyoxal-derived AGEs - Ahmad, Saheem; Shahab, Uzma; Ashraf, Jalaluddin M.; Alyahyawi, Amjad R.; Ansari, Mohammad Azam; Fatma, Sana; Alshammari, Ahmed; Akasha, Rihab; Asiri, Sarah; Puri, Paridhi; Khanam, Afreen (Frontiers in Nanotechnology, 2025)
The nonenzymatic glycation process initiates a harmful cycle that generates various intermediate compounds, leading to carbonyl and oxidative stress, and ultimately resulting in the formation of advanced glycation end products (AGEs). AGEs have been implicated as key factors in the development of several diseases, including neurodegenerative conditions like Parkinson’s and Alzheimer’s diseases, as well as complications associated with diabetes. Given the potential impact of AGEs on these diseases, this study explores the role of copper ferrite nanoparticles (CuFe2O4NPs) in inhibiting the formation of these harmful intermediates and AGEs. Magnetic CuFe2O4 nanoparticles were synthesized using Aloe vera leaf extracts and their effects on AGE formation were assessed. Using both biophysical and biochemical approaches, the study demonstrates that CuFe2O4 NPs have significant anti-glycation properties, which help reduce or prevent AGE formation while maintaining protein structure. These findings suggest that CuFe2O4 NPs may offer therapeutic potential in addressing AGE-related diseases, particularly those linked to diabetes and its complications.